Acid/based indicators from the leaf extracts of Hemigraphis alternata, Iresine herbstii cv., Setcreasea pallida, and aerva sanguinolenta BL. - Marla, Christine Anne J. (2003.)
Plant extracts were prepared from the Philippine ornamental plants dahong-pula (Hemigraphis alternata), blood leaf (Iresine herstii cv.), purple heart (Setcreasea pallida), and bagat-bagat (Aerva sanguinolenta BI.). Among the three solvents---water, methanol, and acetone---used in the extraction of the plant pigments, water was found to be the best solvent., The pH range of each leaf extract was determined with the use of buffer solutions at pH 1.0 up to 13.0. Based on the color changes they exhibited in the buffer solutions, all four (4) plant extracts are possible substitutes to phenolphthalein in the standardization of 0.1 N NaOH while only dahong-pula could be used as substitute to methyl red in the standardization of 0.1 N HCI. One-way ANOVA at a=0.05 showed that there is a significant difference in the mean normality of 0.1 N NaOH obtained usng phenolphthalein, dahong-pula blood leaf, purple heart, and bagat-bagat indicators. The Least Significant Differences showed there is a significant difference between phenolphthalein and the bagat-bagat indicator while the rest are not significant. Therefore, dahong-pula, blood leaf, and purple heart indicators can replace phenolphthalein in the standardization of 0.1 N NaOH. t-Test of Independent means at a=0.05 showed that there is significant difference between the mean normality of 0.1 N HCI obtained using dahong-pula and that obtained using methyl red. Hence, dahong-pula indicator is not a good substitute to methyl red in the standardization of 0.1 N HCI. Dahong-pula pigment was utilized in the preperation of crude pH paper and pH pellet. The red crude pH paper turned green in base while the pH pellet in silca, pink in acid, turned green in base.
Thesis (Undergraduate, Bachelor of Science in Chemistry) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Hemigraphis alternata -- Leaf extracts; Iresine herbstii -- Leaf extracts; Setcreasea pallida -- Leaf extracts